Monetary Policy and Uncertainty about the Natural Unemployment Rate - Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Inflation-targeting central banks have only imperfect knowledge about the effect of policy decisions on inflation. An important source of uncertainty is the relationship between inflation and unemployment. This paper studies the optimal monetary policy in the presence of uncertainty about the natural unemployment rate, the short-run inflation-unemployment tradeoff and the degree of inflation persistence in a simple macroeconomic model, which incorporates rational learning by the central bank as well as private sector agents. Two conflicting motives drive the optimal policy. In the static version of the model, uncertainty provides a motive for the policymaker to move more cautiously than she would if she knew the true parameters. In the dynamic version, uncertainty also motivates an element of experimentation in policy. I find that the optimal policy that balances the cautionary and activist motives typically exhibits gradualism, that is, it still remains less aggressive than a policy that disregards parameter uncertainty. Exceptions occur when uncertainty is very high and in inflation close to target.
urn:nbn:de:hebis:30-10119
Keywords: E52; E24; D8; C61; 330; monetary policy; inflation targeting; parameter uncertainty; optimal learning; natural unemployment rate